History Learning by Teachers with Non-History Education Backgrounds at Private High Schools in Demak Regency - Sumarsono, Soni; Romadi, Romadi (Universitas Negeri Semarang, 2020)
This study aimed (1) to assess the preparation and understanding of teachers' educational background in the nonhistory of the teaching of history, (2) to assess learning by teachers' educational background in non-historical, (3) to determine the constraints experienced anything by history teachers A non-historical educational background in history learning. This study used qualitative research methods, emphasizing techniques such as interviews with sources of private high school teachers from three Demak, SMA PGRI Demak, Demak Muhammadiyah High School, and High School Demak Islamic Center. The results of this study indicate that teachers who administer history are teachers who believe in Civics education and Education SOSANT, while for the three high school history education in Private Demak yet. Often, teachers also need help providing materials to students; the lack of historical material makes teachers only provide dibuku material. Students usually feel saturated with history learning because they think history is a rote subject, so they are lazy in learning. From the study results, the school should be more supportive of learning history by complementing other learning resources so that teachers of history lessons will not feel the lack of material. Teachers must be able to overcome the implementation of learning that will take place so that learning history can run smoothly.